Volumetric interpretation of 3D hard rock seismic data - Hossain, M.; Urosevic, Milovan; Kepic, Anton (CSIRO, 2013)
Seismic reflection method has been successfully used in the petroleum industry for the last few decades. Until recently, the mining industry has been reluctant to use seismic methods for mineral exploration because of its high cost, uncertain performance, and potentially ambiguous interpretation results. However, shallow mineral reserves are depleted and exploration is moving towards deeper targets in order to extend existing and to find new mineral reserves. In that space it is perceptible that seismic method will become an important if not primary exploration tool to delineate subsurface structures hosting ore bodies. One of the outstanding issues along the application of seismic methods for mineral exploration is our ability to grasp and then interpret excessively complex seismic images. Volumetric interpretation is performed in 3D, in real–time by applying opacity and transparency filters to grasp the global structures and by rotating and viewing the seismic volume from different angles which allows in–depth understanding of the volume analysed. This, initial stage of volumetric interpretation is followed by more specific tasks aimed towards mapping the interfaces and associated structures of exploration interest. The ore shoots or occurrences are predicted by numerical modelling based on the priori knowledge. The targeting strategy is constructed according to the numerical response and map of the main interfaces and structures. This, for hard rock, novel interpretation methodology is aimed towards direct targeting and estimates of the ore reserves. The implementation is demonstrated on the field data from Kambalda, WA.